Patent sufficiency a UK and European perspective - Atkinson, Jonathan D.M. (Henry Stewart Talks, 2021)
An introduction to patents, Criteria for an invention to be patentable, The concepts of sufficiency and insufficiency in patentability, Sufficiency in the UK compared to Europe, Discussion of case law in UK, Europe and US, Practicalities when preparing a patent specification